PENGARUH GANGGUAN PRIBADI, GANGGUAN EKSTERN DAN GANGGUAN ORGANISASI TERHADAP INDEPENDENSI AUDITOR PADA INSPEKTORAT PROVINSI RIAU - Annisa Agelina; Yusralaini '; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to invetigate the effect of personal disturbance, externaldisturbance and organizationaldisturbance on the the auditors’ independence inInspectorate Riau Province. This study is population. While responden is consisted by the fourty inspectorate officers in Inspectorate Riau Province. The data was collected by distributing quetionnaires which isgiven to 40repondents, but only 39 (97.5%) respondents who fill out the questionnaires completely and can be processed. The analysis tool used is multiple regression using SPSS program version 21. Based on t test results partially be known that the results of t test for variables personal disturbancewas significantly on auditor independence wich t hitung>t table,t test for variables externaldisturbance was significantly to auditors independence and t test for variables organizational disturbance also have significant effect on auditor’s independence. The magnitude of the effect caused by Adjusted R2 by three variables together against the dependent variable 69,9%, while the remaining 30,1% is influenced by other variables not examined in this study.Keywords: Personal Disturbance, External Disturbance,   Organizational Disturbance and The Auditors’ independence